(untitled) (Cambridge, UK, 2001)
The book provides a review of food process modeling, which allows analysts to understand food processing more precisely and allows for better predictions. Features a mixture of theory and practice for professionals in modeling, as well as other food quality professionals
Tin học ứng dụng - CNTP
Keywords: Food industry and trade; Production control,Mathematical models